Pengaruh Celebrity Endorser terhadap Minat Beli Produk Scarlett pada Mahasiswa - Aldila Nur Astari; Ellyawati, Noor; Rahayu, Vitria Puri; Ruspian (Faculty of Teacher Training and Education, Mulawarman University, 2024)
One way to increase sales and increase the popularity of Scarlett Whitening is to work with public figures or celebrities as celebrity endorsers. This study aims to determine the effect of celebrity endorsers on buying interest in Scarlett products in Economic Education students at Mulawarman University. This study uses an ex-post facto method with a quantitative approach, the data uses a sample of 137 respondents through a questionnaire distributed online using Google Form. The research method used is simple linear regression. . The results of research on the use of celebrity endorsers on buying interest in Scarlett Whitening products obtained an average value of the good category. The indicator with the highest value is the visibility indicator (popularity) and the lowest is the power indicator (strength). The results also show that celebrity endorsers have a positive and significant influence on buying interest in Scarlett products at 0.000 <0.05 and the value of Thitung 9.935> Ttabel 1.977. The conclusion of this study is that celebrity endorsers partially play an important role in increasing students' buying interest.